Epistemic preparedness - Seye Abimbola; Tamara Giles-Vernick; Rachel Yang; Mark Stoové; Kari Lancaster; John Noel Viana; Catherine Waldby; Freya L Jephcott; Warwick Anderson; Sonja van Wichelen; Rachel A Ankeny; Lukas Engelmann; et al. (BMJ Global Health)
Preparedness strategies for emergent infectious diseases have focused on microbial surveillance, medical stockpiling and healthcare infrastructure resilience. But what does it mean to be epistemically or cognitively prepared for the next disease outbreak? Taking stock of lessons for data practices and statistical modelling in the wake of COVID-19, we propose a reconceptualising of preparedness in global health, focusing on ecological and sociological configurations or framings rather than resorting to reductive ‘crisis technologies’. We address three problem areas: data collection and sharing, outbreak modelling and the spatiotemporal structuring of analysis and intervention. We take these as illustrative of troubling effects of conceptual inflexibility. We inquire into alternative data practices and more complex epidemiological framings. This refiguring of our cognitive toolkit implies working through colonial legacies and national limitations embedded in governance of epidemiological reasoning. Epistemic preparedness—focusing on a more diverse, equitable and inclusive stocktaking as much as stockpiling—provides a reliable foundation for future disease outbreak management.